Dampak Tes Karakteristik Pribadi (TKP) dalam Seleksi CPNS Metode Computer Assisted Test (CAT) BKN terhadap Profesionalisme ASN - Sugianto, Andri; Mulyaningtyas, Ratna Dewi (Otonomi, 2026)
The Personal Characteristics Test (Tes Karakteristik Pribadi/TKP) is one of the key components of the Basic Competency Selection (Seleksi Kompetensi Dasar/SKD) for Civil Servant Candidates (CPNS) administered through the Computer Assisted Test (CAT) system of the National Civil Service Agency (BKN). TKP assesses dimensions such as personality, integrity, public service, networking, socio-cultural adaptability, information technology proficiency, professionalism, and anti-radicalism attitudes that are relevant to the demands of the State Civil Apparatus (ASN) profession. This study aims to analyze the effect of TKP scores on the professionalism level of ASN in the Kediri Regency Government, as measured by the ASN Professionalism Index (Indeks Profesionalitas ASN/IP ASN). The research employed a quantitative approach using secondary data from the 2021 CPNS selection results and the 2024 IP ASN assessment. Data analysis was conducted using multiple linear regression. The results show that TKP scores have a positive and significant effect on ASN professionalism, with the largest contribution compared to other SKD components. These findings highlight the role of TKP as a key indicator in the ASN recruitment process, correlating with post-appointment performance and work ethic. The study recommends maintaining and improving the quality of the TKP instrument to ensure greater adaptability to the challenges of modern public service.